KENDALA SERTA FAKTOR PENDUKUNG KEBERHASILAN PEMBANGUNAN HUTAN KOTA - J. M. Sri Hardiatmi (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2009)
ABSTRACT City Forest is an area which contains physical component and vegetation and also tress as one ecosystem unity with the function to increase the quality of the living things. That area has a function as a supporting factor of water, air, flora and fauna which has esthetic value in a green growing area. The problem arises in the urban area basically is economical problem where the green land conversion happened into another usage which is more promising economically. The concept to rebuild the City Park/ city forest is always failed, because there are still many different point of view about the definition on the city forest itself and also because the decrease in number of the green open space due to the very strong economical oriented development. To aim the success of the city park development program, it needs several things such as : support from the government wisdom, so there will be a good coordination in the national and district level for the sake of city park management.Financial supports form the APBN, APBD, rejuvenation budgeting (special allocation fund), etc.Program arrangement wisdom. The coordination from the central levels such as; DITJEN RLPS Forestry Ministry, BAPPENAS, Foreign Ministry, and also Domestic Ministry is very important to support of the City Forest development. The program in each city needs a good technical coordination from the forestry Ministry, BAPPEDA, BAPEDAL, and the entire related institution. Key words: City Forest, Green space conversion, City Forest reservation.